2016
DOI: 10.1016/j.bone.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrichment of microRNAs in extracellular matrix vesicles produced by growth plate chondrocytes

Abstract: Matrix vesicles (MVs) are membrane organelles found in the extracellular matrix of calcifying cells, which contain matrix processing enzymes and regulate the extracellular environment via action of these enzymes. It is unknown whether MVs are also exosomic mediators of cell-cell communication via transfer of RNA material, and specifically, microRNA (miRNA). We investigated the presence of RNA in MVs isolated from cultures of costochondral growth zone chondrocytes. Our results showed that the average yield of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 79 publications
4
52
0
Order By: Relevance
“…A similar line of reasoning might apply to many other MV proteins, among them TNAP, which can stimulate not only mineralization but may also affect cell differentiation. The presence of microRNA (miRNAs) in MVs [144] suggests that MVs can function as signalosomes in cell-cell communication during cartilage and bone development via transfer of specific miRNAs. However, it remains to be determined whether such cell-cell communication occurs in vivo .…”
Section: Properties and Functions Of Mvsmentioning
confidence: 99%
“…A similar line of reasoning might apply to many other MV proteins, among them TNAP, which can stimulate not only mineralization but may also affect cell differentiation. The presence of microRNA (miRNAs) in MVs [144] suggests that MVs can function as signalosomes in cell-cell communication during cartilage and bone development via transfer of specific miRNAs. However, it remains to be determined whether such cell-cell communication occurs in vivo .…”
Section: Properties and Functions Of Mvsmentioning
confidence: 99%
“…In addition to growth factors, recent research suggests that extracellular vesicles (EVs), such as exosomes and matrix vesicles (MVs), could be present in and influence the chondroinductivity of cartilage ECM. MVs have been recognized to be present in cartilage ECM as a nucleation site for the initiation of cartilage calcification in endochondral bone formation, but recent work to characterize the content of MVs in chondrocytes found that they can contain growth factors, proteins, matrix metalloproteinases (MMPs), and microRNA (miRNA) relevant to chondrogenesis . The predicted targets of this miRNA suggest the functions of exosomes and MVs are related to regulating chondrogenesis via several signaling pathways (PI3K–AKT, focal adhesion, hypoxia‐inducible factor‐1 (HIF‐1), TGF‐β, and insulin and WNT signaling), in addition to regulating chondrocyte apoptosis, proliferation, differentiation, and matrix formation and degradation .…”
Section: Devitalized Cartilage Matrixmentioning
confidence: 99%
“…A recent study showed that miR-21 is one of the two most abundant miRNAs in the proliferative zone, dominating over 60% of the miRNA pools [122]. Overexpression of miR-21 was reported to promote chondrocyte proliferation and matrix synthesis; interestingly, miR-21 was found to be reduced by food restriction [48] and to target GDF-5 in chondrocytes [115].…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%
“…Mice lacking Dicer in their cartilage had many skeletal defects during development [120], and Dicer has been found to significant ly affect limb size and morphogenesis [121]. Numerous miRNAs were shown to be expressed in the GP, both during embryonic development and subsequently [48, 122]. Interestingly, several miRNAs have recently been found to be specifically enriched hundreds or even thousands of times in MVs, with specific enrichment for miR-122, miR-223, and miR-451, all shown to inhibit proliferation of cells, suggesting that these miRNAs may be critical components in chondrocyte gene regulation networks [122].…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%
See 1 more Smart Citation